Simulation of dynamic recrystallization in an Al-Mg-Si alloy during inhomogeneous hot deformation. (December 2021) - Li, Jiachen; Wu, Xiaodong; Liao, Bin; Cao, Lingfei
Abstract: The hot deformation behaviors of Al-Mg-Si alloys were studied at temperatures of 400–550 °C and strain rates of 0.001–1 s −1 . The microstructure of the compressed samples was characterized by electron back scattered diffraction (EBSD). It was found that the strain distribution was inhomogeneous in the hot compress samples, which caused inhomogeneous dynamic recrystallization fraction (XDRX ) at different position of the sample. The geometrically necessary dislocation (GND) density was calculated from EBSD results by a MATLAB toolbox MTEX. GND densities increased with the increase of strain rate and strain, and the decrease of temperature. A constitutive equation was obtained from experimental stress-strain curves. The parameters for a dynamic recrystallization (DRX) kinetic model were determined considering the inhomogeneous XDRX at different position of the sample. The experimentally acquired constitutive relation and DRX model were imported to commercial software DEFORM-3D to simulate the hot compression tests, and the results agreed well with experimental observations. Finally, the industrial hot extrusion were simulated to further validate the DRX model.